Efektivitas Pelatihan Online untuk Tenaga Pendidik Nonformal dalam Meningkatkan Penerimaan Teknologi Pembelajaran Daring - Gerungan, Azalia; Purba, Herman; Giovani, Dessylia Cindy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
As digitalization characterizes the education field, online learning technology has now become a priority to be tackled by all educators. Therefore, teachers’ capabilities must be upgraded to meet the ability of students in online learning. Formal, nonformal, and informal educators most likely experience the same struggle when it comes to digital competency. Thus, some lecturers of online learning communication science were conducting a year of training that is suitable for the digital capabilities needed by non-formal educators of Bimbel GKY Puri. The longitudinal study is implemented by giving pre-training questionnaires and post-training questionnaires to the educators to measure the change in their technology acceptance. Davis’ Technology Acceptance Model is adopted as the theoretical basis of this research. The result shows that there was no significant change in technological acceptance as age becomes a moderating factor which affects their perceived ease of use influence towards attitudes towards using and their behavioral intention. In the end it was also found that the change in perceived ease of use and perceived usefulness has some effects on behavioral intentions and attitude towards using technology.